Developing and validating Next Generation Science Standards‐aligned learning progression to track three‐dimensional learning of electrical interactions in high school physical science. Issue 4 (13th October 2020) - Kaldaras, Leonora; Akaeze, Hope; Krajcik, Joseph
Abstract: The Framework for K‐12 science education (The Framework ) and Next Generation Science Standards (NGSS) emphasize the usefulness of learning progressions in helping align curriculum, instruction, and assessment to organize the learning process. The Framework defines three dimensions of science as the basis of theoretical learning progressions described in the document and used to develop NGSS. The three dimensions include disciplinary core ideas, scientific and engineering practices, and crosscutting concepts. The Framework defines three‐dimensional learning (3D learning) as integrating scientific and engineering practices, crosscutting concepts, and disciplinary core ideas to make sense of phenomena. Three‐dimensional learning leads to the development of a deep, useable understanding of big ideas that students can apply to explain phenomena and solve real‐life problems. While the Framework describes the theoretical basis of 3D learning, and NGSS outlines possible theoretical learning progressions for the three dimensions across grades, we currently have very limited empirical evidence to show that a learning progression for 3D learning can be developed and validated in practice. In this paper, we demonstrate the feasibility of developing a 3D learning progression (3D LP) supported by qualitative and quantitative validity evidence. We first present a hypothetical 3D LP aligned to a previously designed NGSS‐based curriculum. We further present multiple sources of validity evidence for the hypothetical 3D LP, including interview analysis and item response theory (IRT) analysis to show validity evidence for the 3D LP. Finally, we demonstrate the feasibility of using the assessment tool designed to probe levels of the 3D LP for assigning 3D LP levels to individual student answers, which is essential for the practical applicability of any LP. This work demonstrates the usefulness of validated 3D LP for organizing the learning process in the NGSS classroom, which is essential for the successful implementation of NGSS.